Revendiquer un point de vue situé. L’exposition « Tanesashi: Remembrance of the Shore » à Aomori en 2013 et la série photographique de Sasaoka Keiko - Catherine Grout (Ebisu: Études Japonaises)
In 2013, due to the inclusion of the Tanesashi (Tōhoku) shoreline in the Sanriku Reconstruction National Park, the curator of the Aomori County Museum of Art, Takahashi Shigemi, organized the exhibition “Tanesashi: Remembrance of the Shore”. Her intention was to present a point of view anchored in the region and its history to explore the reality of the lived environment. This view of the region differs from its status as a tourist attraction, inscribing it with a sense of the region’s long history. The aesthetic analysis in this essay focuses, first, on photographs by Sasaoka Keiko. Second, it will analyze the texts published in the exhibition’s accompanying catalogue. This article sets out to study the power dynamics at play in representations of landscape, as well as the potential for resistance to the process of (colonial) territorial appropriation by the central government inherent in such representations.